Thes-economic impact of the phasing out of plantations in the Western and Southern Cape regions of South Africa : a case study of three plantations. - De Beer, Margareta Caterine (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScFor)--Stellenbosch University, 2012.